ANALISIS DAYA SAING USAHATANI TEBU DI PROPINSI JAWA TIMUR - ARIANI, MEWA; ASKIN, ANDI; HESTINA, JUNI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 1 Februari 2006)
In the aspect of sugarcane farming system, increasing productivity and sucrose content of sugar cane (rendemen) are exactly needed to increase the productivity of sugar and farmer incomes. The objective of the research is to analyze competitiveness of farmer’s sugarcane farming system, which is measured by Policy Analysis Matrix (PAM). The research was held on sugar factories in East Java (Pesantren Baru in Kediri, Krebet Baru in Malang, Semboro in Jember, and Pagotan in Madiun). The data are collected by interviewing farmers, 20 farmers in each sugar factory. The results show that farmer’s sugarcane farming systems are financially profitable with average advantage about 2.5-8 million per hectare. Farmer’s advantage in Madiun and Kediri districts are lower than it is in Malang and Jember districts. Although financially sugarcane farming system is profitable, economically it is contrary. Farmer’s financial loss in from 2.0 to 4.0 million per hectare. Sugarcane farming system in Madiun dan Kediri districts are not having comparative advantage (DRCR<1), different from they are in Malang, Jember districts. Sugarcane farming system in Madiun and Kediri districts will have comparative advantage if the productivity is increased by 20 percent or the international sugar price is increased to 220 US$/ton.
Keywords: Sugarcane, Farming System, Competitiveness